1969
DOI: 10.1203/00006450-196909000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Enzymes (GOT and GDH) and Metals (Zn, Mn, and Mg) in Liver of Rats During Endocrine Imbalance and Caloric Restriction

Abstract: ExtractRestriction of essential trace metals in the diet interferes with growth. I n this study the converse conditions pertained. Livers from calorie-restricted and hypophysectomized rats (with or without hormone treatment) were analyzed for protein, ribonucleic acid (RNA), deoxyribonucleic acid DNA), Mn, Zn, and Mg content and for enzyme activity of glutamic oxalic transaminase (GOT) and glutamic dehydrogenase (GDH). The data are expressed per unit of DNA in liver.Hypophysectomized rats had reduced amounts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

1970
1970
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…The highest specific (displaceable by excess unlabelled hormone) binding of 1251I-labelled human somatotropin was found in the liver of the late-pregnant rabbit (Tsushima & Friesen, 1973). This is consistent with several of the known actions of somatotropin, such as the stimulation of somatomedin production (McConaghey & Sledge, 1970) and protein synthesis (Korner, 1959) in the liver, and effects on the activities of certain enzymes in the liver, such as glutamate dehydrogenase (Cheek & Graystone, 1969), ornithine decarboxylase and RNA polymerase (Janne & Raina, 1969).…”
supporting
confidence: 77%
“…The highest specific (displaceable by excess unlabelled hormone) binding of 1251I-labelled human somatotropin was found in the liver of the late-pregnant rabbit (Tsushima & Friesen, 1973). This is consistent with several of the known actions of somatotropin, such as the stimulation of somatomedin production (McConaghey & Sledge, 1970) and protein synthesis (Korner, 1959) in the liver, and effects on the activities of certain enzymes in the liver, such as glutamate dehydrogenase (Cheek & Graystone, 1969), ornithine decarboxylase and RNA polymerase (Janne & Raina, 1969).…”
supporting
confidence: 77%
“…While Zn deficiency may exist in mammals as a definite entity, the hypothesis can be made that in protein deficiency, as with other situations, RNA content of the cell will fluctuate with the Zn content [3].…”
Section: Discussionmentioning
confidence: 99%
“…These interrelations are considered for control rats, In an earlier paper [3] it was reported that during a rats receiving adequate protein but inadequate calories, variety of circumstances affecting growth of rats and for rats that had been hypophysectomized. (endocrine imbalance, calorie restriction) the ratios Regression equations presented in this communicain liver of both zinc and ribonucleic acid to deoxyribo-tion contain a common factor, liver weight, through nucleic acid appeared to parallel each other closely.…”
Section: Introductionmentioning
confidence: 99%
“…This element has been observed to be an integral part of several metalloenzymes including carbonic anhydrase, alkaline phos phatase, pancreatic carboxypeptidase and lactic dehydrogenase. It is also required for synthesis of nucleic acids and protein metabolism [13][14][15][16], Zinc deficiency was once thought impossible in man owing to the wide spread presence of the element in food and water. This concept is now changed.…”
Section: Discussionmentioning
confidence: 99%